Allogeneic Mesenchymal Stem Cells and Its Conditioned Medium as a Potential Adjuvant Therapy for COVID-19 - Wahyu Widowati; Ahmad Faried; Hanna Sari Widya Kusuma; Yulius Hermanto; Ali Budi Harsono; Tono Djuwantono (Cell and BioPharmaceutical Institute, 2023)
Recent research has demonstrated that mesenchymal stem cells (MSCs) potentially benefit and enhance coronavirus disease (COVID-19) recovery. This benefit occurs via a mechanism that promotes viral clearance by phagocytes and macrophages. This action occurs through the innate (increase in IL-10 production and decrease in TNF-α and IL-12 production) and the adaptive immune system (decrease in IL-17 production, promote regulatory T cell proliferation and inhibit effectors T cell proliferation). MSCs are expected to act as an anti-inflammatory in the hyper-inflammatory state of COVID-19. MSCs enhance immune cell replacement that have been overwhelmed or have been lost due to cytokine storm. Although vaccines are the answer to this pandemic, MSCs can improve COVID-19 patients, especially in patients with chronic illnesses. The focus on keeping death-rates low is a great opportunity for MSCs-based therapy for severe or critically ill patients. MSCs and conditioned medium have the potential to serve as adjunctive therapy in preventing the body's overactive defense response or the so-called cytokine storm caused by COVID-19.Keywords: adjuvant therapy, COVID-19, mesenchymal stem cells, secretome